PENERAPAN METODE JUST IN TIME (JIT) DALAM MENGENDALIKAN PERSEDIAAN BAHAN BAKU PADA PABRIK KELAPA SAWIT (PKS) PT. JOHAN SENTOSA BANGKINANG - Rudi Kurniawan; Auzar Ali (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to determine the application of raw material inventory control using the Just In Time (JIT) method at PT. Johan Sentosa Bangkinang so that it can be a reference for the company in the future. The results of the study note that PT. Johan Sentosa in controlling the supply of raw materials is still not optimal, seen from the total inventory costs incurred is still quite large, namely Rp. 253,297,450. While the total cost of controlling raw material supply using the Just In Time (JIT) method is Rp. 71,167,800 and using the EOQ method of Rp. 170,802,719. By using the Just In Time (JIT) method the company is able to save costs by Rp. 182,129,650 or around 72% and using the EOQ method saves inventory costs by Rp. 82,494,731 or around 32%.